Monitoring Growth and Antibiotic Susceptibility of Escherichia coli with Photoluminescence Emitting Semiconductor Biochips. (2017) - Nazemi, Elnaz; Hassen, Walid. M.; Frost, Eric H.; Dubowski, Jan J.
Abstract: Growth and antibiotic sensitivity of Escherichia coli were evaluated with an innovative method based on photocorrosion of biofunctionalized GaAs/AlGaAs quantum well (QW) biochips. The formation of surface oxides and dissolution of a limited thickness GaAs cap material results in the appearance of a characteristic maximum in a time-dependent plot of the photoluminescence (PL) emitting biochip. A position of the PL maximum depends on the electrostatic interaction between bacteria and the biochip surface, and it becomes delayed with increasing concentration of bacteria growing on the biochip surface. We demonstrate detection of the bacteria reaction to antibiotics within less than 3 hours.